2018
DOI: 10.1007/s00384-018-2991-0
|View full text |Cite
|
Sign up to set email alerts
|

Extra nodular metastasis is a poor prognostic factor for overall survival in node-positive patients with colorectal cancer

Abstract: Extra nodal metastasis is an independent prognostic factor in patients with node-positive colorectal cancer. Extra nodal metastasis is associated with high odds of tumor-related mortality and poor overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
4
1
Order By: Relevance
“…As increased complexity was associated with worse prognosis, our results are in line with studies using histopathologic definitions in which the prognosis of both LNMs with ENE and TDs is worse than that of LNMs without ENE. 3,6,14 The finding that tumor nodules with a more complex shape are associated with worse DFS compared with those with a less complex shape is in contrast with a previous study in which it was found that the contour of TDs was not associated with prognosis. 15 However, there are several differences between both studies that should be emphasized.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…As increased complexity was associated with worse prognosis, our results are in line with studies using histopathologic definitions in which the prognosis of both LNMs with ENE and TDs is worse than that of LNMs without ENE. 3,6,14 The finding that tumor nodules with a more complex shape are associated with worse DFS compared with those with a less complex shape is in contrast with a previous study in which it was found that the contour of TDs was not associated with prognosis. 15 However, there are several differences between both studies that should be emphasized.…”
Section: Discussioncontrasting
confidence: 82%
“…This has been identified as a poor prognostic factor compared with LNMs without ENE. 5,6 Additionally, TDs, referred to as isolated tumor aggregates in the fat surrounding the bowel, also have an independent prognostic impact in CRC. 3,4 Currently, ENE is not separately included in the staging of patients with CRC and TDs are categorized in the nodal stage as N1c, only having clinical impact in the absence of LNMs.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that metastasis is an independent predictor for poor prognosis of many cancer types (124126). We find that elevated expression of SIRT1 was correlated with OS, DFS, EFS, and PFS.…”
Section: Discussionmentioning
confidence: 99%
“…This is a retrospective analysis of prospectively collected data of patients undergoing oncologic resection of colorectal cancer. The data of all consecutive patients diagnosed with CRC is prospectively put into an institutional database by trained study nurses and research fellows as reported elsewhere [10, 11]. The database is continuously updated with data on the present status of all registered patients.…”
Section: Methodsmentioning
confidence: 99%